Pulsed laser deposition of high Tc superconducting thin films : Present and future - Wu, X. D. (1990)
Pulsed laser deposition (PLD) has been widely used for deposition of high Tc superconducting thin films, and is recognized as one of the best physical vapor techniques for the preparation of these films. The most important advantage of this technique is stoichiometric deposition; films can be made with the same composition as the target. Utilizing PLD, not only thin films but also multilayers and superlattices of high Tc superconductors have been fabricated. In this paper, the performance of the technique will be reviewed, and speculations regarding the future would be made.